If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -9 = 4x + -5 Reorder the terms: -9 + 6x = 4x + -5 Reorder the terms: -9 + 6x = -5 + 4x Solving -9 + 6x = -5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -9 + 6x + -4x = -5 + 4x + -4x Combine like terms: 6x + -4x = 2x -9 + 2x = -5 + 4x + -4x Combine like terms: 4x + -4x = 0 -9 + 2x = -5 + 0 -9 + 2x = -5 Add '9' to each side of the equation. -9 + 9 + 2x = -5 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = -5 + 9 2x = -5 + 9 Combine like terms: -5 + 9 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| (n+1)(n-7)=0 | | (5x+3)(x-5)=0 | | 8k^2-8=640 | | x^2-1=80 | | k^2=37 | | 5x+6=x+74 | | 5x+40=8x+15 | | 6p^2-3=147 | | X=4p+p/2+p/6-p/90 | | 4n^2+6=158 | | 6x^2=158 | | a^2-8=-7 | | r^2=0 | | 5k^2-20k-64=0 | | a^2+12a-94=0 | | x^2+16x-23=0 | | 3x(4x^2-256)=0 | | x+8-11-3+4=10 | | 5(3-2x)=20 | | 7n^2-10n-53=-5 | | 4b^2+b-66=-6 | | 9k^2-12k-51=-6 | | 3p^2+17p-30=-10 | | 60-10/25=-2 | | 9p^2+19p-66=8 | | 25/x-10=-2 | | 10g-6=7g+12 | | 10a^2-20a-80=0 | | 3k+2=10+k | | 10n^2+20n-30=0 | | r^2-4r-31=0 | | v^2+8v-48=0 |